Protecting seniors against environmental disasters - Greenberg, Michael R., author.
1 online resource (xvi, 210 pages)
Keywords: "This book connects the dots between two powerful trends in the US: the rapid growth of the 65+ year old population and the marked increase in natural and human-caused environmental disasters. Inevitably, these two trends lead to more environmental disasters disproportionately impacting seniors, unless coordinated planning, regulations, and practice focus on identifying best risk management practices and implementing them. Built on a risk analysis framework, this book uses literature, interviews and case studies to find the best lessons learned about how to prevent seniors' exposure to low probability but high consequence events and how to protect the 65+ year old population when these events do occur"--